2012
DOI: 10.1007/s00395-012-0268-2
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation to chronic hypoxia in cardiac mitochondria

Abstract: Chronic hypoxia decreases cardiomyocyte respiration, yet the mitochondrial mechanisms remain largely unknown. We investigated the mitochondrial metabolic pathways and enzymes that were decreased following in vivo hypoxia, and questioned whether hypoxic adaptation was protective for the mitochondria. Wistar rats were housed in hypoxia (7 days acclimatisation and 14 days at 11% oxygen), while control rats were housed in normoxia. Chronic exposure to physiological hypoxia increased haematocrit and cardiac vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
98
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 46 publications
(67 reference statements)
11
98
1
2
Order By: Relevance
“…Curiously, CS activity was normal in both tissues at both durations of hypoxia, however, aconitase activity was more than 50% lower in hypoxic cardiac muscle at both time points, in agreement with a recent finding in the cardiac mitochondria of chronically hypoxic rats (15). Previous studies in lung (43), skeletal muscle (55), brain (5), and nerve cells (53) have indicated that aconitase is particularly susceptible to ROS-mediated inhibition, as are other TCA cycle enzymes such as isocitrate dehydrogenase (28).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Curiously, CS activity was normal in both tissues at both durations of hypoxia, however, aconitase activity was more than 50% lower in hypoxic cardiac muscle at both time points, in agreement with a recent finding in the cardiac mitochondria of chronically hypoxic rats (15). Previous studies in lung (43), skeletal muscle (55), brain (5), and nerve cells (53) have indicated that aconitase is particularly susceptible to ROS-mediated inhibition, as are other TCA cycle enzymes such as isocitrate dehydrogenase (28).…”
supporting
confidence: 91%
“…Alternatively, aconitase has also been shown to undergo reversible modulation by frataxin, an iron-binding protein (40). Previous reports on rat cardiac tissue indicate that total aconitase protein concentration does not change after 2 wk of hypoxia and propose that it is a posttranslational modification that decreases aconitase activity (15). Hypoxic tissues produce ROS as a result of attenuated electron flow through the ETS when oxygen, the final electron acceptor, is limited (33).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia has been shown to decrease mitochondrial respiration in the cardiomyocyte, which is associated with cellular dysfunction (50). Nevertheless, literature addressing mitochondrial subpopulation differences in hypoxic models remains scarce (45). Using a rat model of chronic hypoxia (11% oxygen exposure for 14 days), Heather et al (45) observed a decrease in state 3 respiration rates of both SSM and IFM when using fatty acid and pyruvate as substrates.…”
Section: Pathological Influencementioning
confidence: 99%
“…Another example was that in endothelial cells of mice lower limbs, the formation of cardiovascular induced by ischemia was inhibited when Sirt1 was silenced. Instead, the genes of vascular endothelial growth factor (VEFG) and its receptor 2 (VEFGR2) and nitric oxide synthase were expressed while resveratrol activated Sirt1 [41]. According to above experiments, Sirt1 induces angiogenesis probably by inhibiting forkhead box class O family transcription factor (FoxO1), an essential negative regulatory factor in vascular differentiation.…”
Section: Protein Lysine Acetylation and Cardiovascular Diseasementioning
confidence: 97%